Cultural Synergy in Learning English: Co-Cultural Communication’s Role in Collaborative Learning at Northwest Institute of Health Sciences, Peshawar, Pakistan. - Shagufa; Ali, Muhammad Waqar (Pakistan Languages & Humanities Review)
This study explored how co-cultural communication affects group learning among students at Northwest Institute of Health Sciences, Peshawar. Classrooms today are more culturally diverse. Students from different backgrounds bring unique communication styles which impact their intragroup collaboration. A 5-point Likert Scale questionnaire was employed to collect data 100 undergraduates. The survey asked about culture, communication, and learning satisfaction. Descriptive and regression analysis were used. Divergent views prevail among participants, many preferring working with students from similar backgrounds, others prioritizing solo study. Regression analysis reveals a positive correlation between collaboration and communicative comfort and respect was identified. Communication style predict 18.2% of satisfaction levels. The findings further highlight the salience of respecting communicative diversity, teacher’s role, and learning style for collaborative learning. The findings suggest training for teachers is needed. Culturally aware classrooms support all learners, preparing them for real-world teamwork in diverse healthcare settings.